Stability of Islamic banks in Indonesia: Autoregressive Distributed Lag Approach - Agus Widarjono (University of Merdeka Malang, 2020)
Islamic banks in Indonesia are very vulnerable to the instability of their business processes because of their small market share. Moreover, based on their financial performances, Islamic banks are worse than those of conventional banks due to lower profits (ROA) and higher Non-performing financing (NPF). Our study investigates the stability of Islamic banks. We measure the stability using Z-score and NPF. Instead of an individual bank, the study applies an aggregate data of Islamic banks encompassing Islamic commercial banks along with Islamic business units. Monthly time series data, covering January 2010 to December 2018 are selected. We apply the Autoregressive Distributed Lag (ARDL) model. The findings document that the Islamic bank's specific variables affecting stability are size, CAR, and efficiency. The larger size and CAR support the Islamic bank's stability. Lower efficiency increases the Islamic bank's instability. Meanwhile, Inflation and exchange rates affect the Islamic bank's stability. Economic downturns due to inflation and depreciation of rupiah increase the instability of Islamic banks.JEL Classification: G21, G24 How to Cite:Widarjono, A. (2020). Stability of Islamic banks in Indonesia: Autoregressive Distributed Lag Approach. Jurnal Keuangan dan Perbankan, 24(1), 40-52.DOI: https://doi.org/10.26905/jkdp.v24i1.3932